2014
DOI: 10.1371/journal.ppat.1004333
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive Transfer of EBV Specific CD8+ T Cell Clones Can Transiently Control EBV Infection in Humanized Mice

Abstract: Epstein Barr virus (EBV) infection expands CD8+ T cells specific for lytic antigens to high frequencies during symptomatic primary infection, and maintains these at significant numbers during persistence. Despite this, the protective function of these lytic EBV antigen-specific cytotoxic CD8+ T cells remains unclear. Here we demonstrate that lytic EBV replication does not significantly contribute to virus-induced B cell proliferation in vitro and in vivo in a mouse model with reconstituted human immune system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 50 publications
(70 reference statements)
3
76
0
Order By: Relevance
“…most commonly derived from cord blood, fetal livers or granulocyte–macrophage colony‐stimulating factor (GM‐CSF) ‐mobilized peripheral blood (Fig. ) . Engraftment depends heavily on stem cell origin, injection route, HSC donor, background murine strain, irradiation status and engraftment age.…”
Section: His Micementioning
confidence: 99%
See 1 more Smart Citation
“…most commonly derived from cord blood, fetal livers or granulocyte–macrophage colony‐stimulating factor (GM‐CSF) ‐mobilized peripheral blood (Fig. ) . Engraftment depends heavily on stem cell origin, injection route, HSC donor, background murine strain, irradiation status and engraftment age.…”
Section: His Micementioning
confidence: 99%
“…1). 6 Engraftment depends heavily on stem cell origin, injection route, HSC donor, background murine strain, irradiation status and engraftment age. Most haematopoietic lineages are engrafted, including several myeloid subsets.…”
Section: His Micementioning
confidence: 99%
“…R. Soc. B 374: 20180296 transactivation, it was shown that lytic EBV replication only transiently contributes to viral loads in immunocompetent humanized mice [40] (figure 1). However, lytic EBV replication can be increased by using viruses with similarities to those found in nasopharyngeal carcinoma [45,46].…”
Section: Infection Of Humanized Mice By Epstein-barr Virus and Kaposimentioning
confidence: 99%
“…B 374: 20180296 enables us to investigate the requirements for their development and immune control. High-dose EBV infection (10 5 infectious virus particles) leads to lymphoproliferative lesions in 20 -30% of the infected animals [8,40,41]. These tumours are B-cell lymphomas with latency III EBV gene expression which disseminate from the spleen to liver, kidney, lymph nodes and pancreas [8,39].…”
Section: Infection Of Humanized Mice By Epstein-barr Virus and Kaposimentioning
confidence: 99%
“…In these cell lines EBV antigen specificities that mediate protection are mostly ill-defined and it is assumed that T cells against transforming latent EBV antigens primarily mediate anti-tumor effects after adoptive transfer. Interestingly, recent studies have suggested that some EBV associated malignancies might benefit from lytic EBV infection [28,29] and that lytic EBV antigen specific CD4 + and CD8 + T cells might be able to contribute to EBV associated lymphoma suppression [29,30]. In good agreement, plasma EBV viral loads, which might in part result from virus shedding, correlate with the occurrence and progression of some EBV associated malignancies, including PTLD, Hodgkin’s lymphoma and nasopharyngeal carcinoma [3133].…”
Section: Adaptive Immune Control Of Ebvmentioning
confidence: 99%